2018
DOI: 10.1016/j.wem.2017.12.002
|View full text |Cite
|
Sign up to set email alerts
|

International Commission for Mountain Emergency Medicine Consensus Guidelines for On-Site Management and Transport of Patients in Canyoning Incidents

Abstract: Canyoning is a recreational activity that has increased in popularity in the last decade in Europe and North America, resulting in up to 40% of the total search and rescue costs in some geographic locations. The International Commission for Mountain Emergency Medicine convened an expert panel to develop recommendations for on-site management and transport of patients in canyoning incidents. The goal of the current review is to provide guidance to healthcare providers and canyoning rescue professionals about be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 65 publications
0
7
0
2
Order By: Relevance
“…A recent review compared the use of intravenous and intraosseous access in providers wearing high-precaution PPE, and suggested that in this context intraosseous access is achieved faster (Drozd et al, 2021 ). Intraoesseous access may have limitations during prolonged rescues or in aqueous environments (Strapazzon et al, 2018 ). Additional routes of drug administration have been suggested in mountain rescue.…”
Section: Discussion and Recommendationsmentioning
confidence: 99%
“…A recent review compared the use of intravenous and intraosseous access in providers wearing high-precaution PPE, and suggested that in this context intraosseous access is achieved faster (Drozd et al, 2021 ). Intraoesseous access may have limitations during prolonged rescues or in aqueous environments (Strapazzon et al, 2018 ). Additional routes of drug administration have been suggested in mountain rescue.…”
Section: Discussion and Recommendationsmentioning
confidence: 99%
“…From our data, we cannot conclude whether the risk for tissue infection is increased compared to any other trauma. ICAR-MEDCOM recommends that wounds be cleaned and systemic antibiotics given for open fractures [9]. Tetanus vaccinations should be up to date and are recommended, ideally prior to performing canyoning.…”
Section: Injury Pattern and Severitymentioning
confidence: 99%
“…In 2017, the International Commission for Mountain Emergency Medicine (ICAR MEDCOM) defined consensus guidelines for the on-site management and transport of patients in canyoning accidents, as well as summarising, commenting on and grading the literature available [9]. Although regional data have been reported, no long-term national data on canyoning have been published to date.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, it seems safe and feasible for healthy individuals to perform short-term moderate-strenuous aerobic physical activity while wearing face masks and performing SAR activities such as cardiopulmonary resuscitation (CPR) (Rauch et al, 2021 ), ground transport, and winch operations. PPE could however increase the burden of increased body temperatures and heat-related illnesses, especially in a hot climate or in canyoning rescues (Strapazzon et al, 2018 ; Lipman et al, 2019 ). In addition, when wearing PPE, the face is partially covered and therefore communication among rescuers could be less effective (Hüfner et al, 2021), especially during acute management (Lim et al, 2020 ).…”
Section: Current Mitigation Strategies and Possible Pitfallsmentioning
confidence: 99%
“…New PPE protocols against airborne infectious diseases should be compatible with technical equipment and specific environments such as snow and water in an avalanche, canyoning, or cave rescue (Schneider et al, 2016 ; Strapazzon and Brugger, 2018 ; Strapazzon et al, 2018 ). Disposable garments are fragile and do not stand up to the wear and tear of the prehospital wilderness environment.…”
Section: Current Mitigation Strategies and Possible Pitfallsmentioning
confidence: 99%